INNOVATIVE PROTECTION AGAINST THE SCOUR AT OUTLETS OF CYLINDRICAL CULVERTS AND APPLICATION USING MULTI EXPRESSION PROGRAMMING TECHNIQUE (MEP) - M.A, Nassar (Engineering heritage journal, 2022)
The present experimental study suggested a pool to resist the localized scour downstream of cylindrical culverts. The study was conducted with a range of intensity number of discharges = [0.44:0.98]. The proposed pool decreased the scour by 70%. The pool of the comparative depth = 0.29 gives the minimal geometrics of the scour hole. The pool length has a significant influence on the scour depth. Multi Expression Programming (MEP) is utilized to develop predicting equations of the erosion geometrics. The proposed models were compared with Multiple Linear Regression (MLR). The average precision of the equations improved by 8% more than multiple linear regression equations (MLR).